Perwujudan Takamul, Wasathiyah Dan Harakah Dalam Ekonomi Islam - M. Tolib Alawi (STAI Siliwangi Bandung, 2016)
Islam is a perfect religion, balanced and dynamic, therefore there will be no longer able to enhance the Islamic religion, both in terms of law and culture. Islam pioneered by the prophet Muhammad was born as Rahmatul lil Alamin. As Rahmatul lil Alamin Islam has a legal system that has the characteristics and distinctive characteristics. The hallmark of Islamic law itself is Takamul, Wasathiyah and Harokah. Takamul in Islam is to have a perfect legal system / unanimously, the Islamic law has been to measure and regulate the human from birth until he faces Allah SWT. Wasathiyah in Islam is draw / harmony, that harmony with Allah SWT, in harmony with humans, and in harmony with nature. If the harmony can be realized in the world so can in the hereafter. And Harokah in Islam is moving and evolving with the times. All three of the Islamic legal system deals with various aspects of human life, whether it is related to worship and muamalah.